Genetic studies and physiological responses to ultraviolet radiation in the Bacteroides fragilis group - Jones, David Todman (Rhodes University, Faculty of Science, Department of Biochemistry and Microbiology, 1980)
The contents of this thesis have been divided into 2 parts . The first part deals with genetic studies carried out on 36 strains belonging to the Bacteroides fragilis group. A number of mutants were isolated from several of the strains. A notable feature of the methods used was the low yield of mutants obtained and the marked sensitivity of these organisms to the mutagenic agents. Variations in colonial morphology was found to be a common feature amongst these organisms. In a few strains this phenomenon was clearly visible, in the remainder it was much weaker, and often could only be seen with the aid of a microscope . Colonial variation was found to be due to the ability of a proporti on of the cells to pruduce capsules or slime layers. The variants were found to segregate at high frequency and different growth conditions were found to have little effect on the segregation frequency or capsule formation . A number of phages specific for B. fragilis and B. t hetaiotaomicron were isol ated. All these phages were virulent and attempts to induce lysogenic phages were unsuccesful . The use of these phages in attempts to obtain transduction proved unsuccessful. A phage carrier state was found to occur in the majority of the phage-host cell systems, which seemed to be due to the presence of phage-resistant encapsulated cells in the population. Bacteriocins were produced by about half the strains, these inhibited the growth of a high proportion of the 36 strains tested. The bacteriocins were released into the growth media at the end of the growth period in the 2 bacteriocins tested. A link between the mode of action of one bacteriocin and rifampicin-resistance was investigated. All the bacter iocins tested were found to be inactive against some rifampicin-resistant mutants of a susceptible strain, suggesting a common mode of action. The presence of capsules in some cells appeared to confer bacteriocin-resistance on these variants. The second part of the thesis deals with a study of the physiological responses of a single strain of B.fragilis to ultraviolet radiation. This strain was found to be more sensitive to ultraviolet radiation under aerobic conditions. The amount of pyrimidine dimers formed after irradiation under anaerobic and aerobic conditions, was not found to differ significantly, indicating that the increase in sensitivity under aerobic conditions was not due to an increase in DNA damage. The use of repair inhibitors and the survival characteristics indicate that this difference was due to decreased repair capabilities under aerobic conditions. Liquid holding recovery in B.fragiZis was found to occur under aerobic conditions . This process was brought about by excision repair and appeared to be due to a decrease in repair efficiency under aerobic conditions. Under anaerobic conditions, where full repair capabilities were present, liquid holding recovery was inhibited. Both minimal medium recovery and fluence dependent filament formation were found to occur in irradiated B.fragiZis cells. The survival kinetics of a number of irradiated B.fragiZis phages were determined and a number of phage reactivation processes were investigated. Little or no host cell reactivation appeared to occur in the strains investigated, however, some ultraviolet reactivation and multiplicity reactivation was found to occur, but only under anaerobic conditions. Photoreactivation was found to be absent in this organism, but an excision repair system was present . The excision repair system was partially characterized and was found to resemble short patch excision repair in E.coli. Evidence was found which suggested that a second mode of repair which was sensitive to oxygen, also occurred in this strain. This repair system which appeared to be responsible for error-prone repair, and the systems which were responsible for ultraviolet reactivation and multiplicity reactivation, seemed to be dependent on a recombination function' which was inhibited by oxygen. The significance of this finding for future genetic studies was discussed.
Keywords: Bacteroides; Ultraviolet radiation